Substitusi Sebagian Pupuk Kimia dengan Pupuk Organik Hayati pada Jagung (Zea mays): Partly Substitution of Chemical Fertilizer with Bio-organic Fertilizer on Maize (Zea mays) - Syah Deva Ammurabi; Iswandi Anas; Budi Nugroho (Jurnal Ilmu Tanah dan Lingkungan, 2020)
High amount of chemical fertilizer application simultanously caused soil degradation and environmental pollution. Bio-organic fertilizer application increases nutrient availability, improve soil properties, promote plant growth and increase yield. This study aims to understand effects of chemical fertilizer substitution with bio-organic fertilizer application on growth, uptake of N, P, K, and agronomic efficiency of maize in vegetative phase. Pot experiment was conducted at IPB Cikabayan Experimental Station, Dramaga, Bogor. Laboratory analysis was done at Department of Soil Science Laboratory, Faculty of Agriculture, Bogor Agricultural University (IPB). Randomized Block Design with single factor was used in this experiment. The treatments were: Control, POH (bio-organic fertilizer only), POH + 50% (NPK), POH + 100% (NPK), 50% (NPK) , and 100% (NPK). Bisma maize variety was used as plant indicator. Five weeks after transplanting, the biomass (shoot and roots) biomass ware harvested. NPK uptake analysis was performed to shoot samples. Results showed that bio-organic fertilizer application reduced the rate of chemical fertilizer by 50% and increase N, P, and K uptake. Combination between bio-organic fetilizer and 50% chemical fertilizer had the highest agronomic efficiency. Bio-organic fertilizer substitute 50% chemical fertilizer of maize.